MALE AND FEMALE ROLE IN CONVERSATION OF THE STUDENTS AT ENGLISH LANGUAGE EDUCATION DEPARTMENT OF GUNUNG RINJANI UNIVERSITY: A LINGUISTIC FEATURE OF SPOKEN DISCOURSE STUDY - LALU NURUL YAQIN, M. ZAINUDDIN (LPPM Universitas Gunung Rinjani, 2020)
This research aims at investigating the characteristics of male language in its comparison tofemale language. The analysis was focused on the analysis of conversations in order to findout any significant features of male and female language which was used in the classroomdiscussion. The research design and analysis was a case study, with a descriptivequalitative approach. This study was focused on discovery, insight and understanding of thelanguage facts in male and female language. Men and Female language here were in theforms of conversations which involved the male and female. The data finding and discussionof the research, which relates to research questions proposed in chapter one. The first andsecond research questions are concerned with the linguistics feature of male and femaledifferences in conversation. Based on the numerous the transcriptions of conversationalfeatures were identified. The transcript of each participant was examined to ascertain whichlinguistics features were exhibited. Out of these, six of these linguistic features wereselected for discussion and analysis, and relevant excerpts were selected as representativeexamples. The linguistics features which have been selected for discussion, such as: (1)minimal responses (2) overlaps (3) repetitions (4) self-repairs (5) interruptions (6)conversational breakdown. The results indicate that there were any linguistic featuresdifferences between male and female in conversation during the question and answersession in the class group discussion of the students in the University of Gunung Rinjani.Keywords: male and female, role in conversation, linguistic featureABSTRAKPenelitian ini bertujuan Investigasi perbandingan karakteristik bahasa laki-laki untuk bahasaperempuan. Analisis ini difokuskan pada analisis percakapan dalam rangka untukmengetahui segala fitur yang signifikan dari bahasa pria dan wanita yang digunakan dalamdiskusi kelas. Desain penelitian dan analisis yang digunakan adalah studi kasus, denganpendekatan deskriptif kualitatif. Penelitian ini difokuskan pada penemuan, wawasan danpemahaman tentang fakta bahasa dalam bahasa pria dan wanita. Bahasa Pria danPerempuan di sini adalah dalam bentuk percakapan yang melibatkan laki-laki danperempuan. Data tersebut menemukan dan diskusi tentang penelitian, yang berkaitandengan pertanyaan penelitian yang diajukan dalam bab satu. Pertanyaan penelitian pertamadan kedua prihatin dengan fitur linguistik dari perbedaan laki-laki dan perempuan dalampercakapan. Berdasarkan berbagai transkripsi fitur percakapan diidentifikasi. Transkripsetiap peserta Diperiksa untuk memastikan yang linguistik fitur yang dipamerkan. DariUlasan ini, enam dari Ulasan linguistik fitur ini dipilih untuk diskusi dan analisis, dan Kutipanyang relevan dipilih sebagai contoh representatif. Linguistik fitur yang telah dipilih untukdiskusi, seperti: (1) respon minimal (2) tumpang tindih (3) pengulangan (4) self-perbaikan (5)interupsi (6) rincian percakapan. Hasil penelitian menunjukkan bahwa ada perbedaan antarafitur linguistik pria dan wanita dalam percakapan selama sesi tanya jawab dalam diskusikelompok kelas mahasiswa di Universitas Gunung Rinjani.Kata kunci: laki-laki dan perempuan, peran percakapan, fitur linguistik